Reality of Change Leadership among Elementary School Principals in the City of Rahat in the Negev: from the point of view of Teachers - Abu Freach, Anahed Mohamed (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the extent to which elementary school principals in the city of Rahat in the Negev region practice change leadership from the perspective of their teachers. A descriptive-analytical quantitative approach was adopted, utilizing a questionnaire consisting of 40 items distributed across six domains: the necessity for change, strategic vision, building a supportive organizational culture, motivation, human relations, and the implementation and follow-up of change. The validity and reliability of the instrument were confirmed, with a Cronbach’s alpha coefficient of 0.985. The questionnaire was administered to a purposive random sample of 50 teachers, and data were analyzed using SPSS. The results indicated that the overall level of change leadership practices was high (mean = 3.86), with the "motivation for change" domain ranking first (mean = 3.97), followed by the "human relations and role model" domain (mean = 3.93). Additionally, no statistically significant differences were found in the degree of change leadership practices based on gender, academic qualification, or years of experience, suggesting a consensus among teachers regarding the principals’ efforts. These findings reflect successful change leadership practices, with recommendations to enhance leadership training, support communication between principals and teachers, and address weaknesses in school performance.